Represent the arithmetic series using the recursive formula. 94, 81, 68, 55, …

f(n) = f(n − 1) + (13)
f(n) = f(n − 1) + (−13)
f(n) = f(1) + (13)
f(n) = f(1) + (−13)

Respuesta :

Answer:

[tex]f(n) = f(n - 1) - 13[/tex]

Step-by-step explanation:

The given sequence is 94, 81, 68, 55, …

We can observe that, there is a constant difference among the subsequent terms:

[tex]d = 81 - 94 = - 13[/tex]

The sequence is therefore an arithmetic sequence with first term:

[tex]f(1) = 94[/tex]

The recursive formula is given by;

[tex]f(n) = f(n - 1) + d[/tex]

We just have to plug in d=-13 to get:

[tex]f(n) = f(n - 1) - 13[/tex]

Answer:

f(n)=f(n-1)=(-13)

Step-by-step explanation:

got it right on flvs